Living in Harmony: Acculturation of Balinese and Dayak Ngaju Cultures in Basarang Jaya Village, Central Kalimantan - Sutrisno, Herwin; Hardiman, Gagoek; Pandelaki, Edward Endrianto; Susi, Theresia (Jurnal Ilmiah Peuradeun, 2019)
The transmigrants of Balinese ethnic living in Basarang Jaya Village, Kapuas, Central Kalimantan live harmoniously with the local ethnics (Dayak Ngaju) even though the area ever experienced ethnic riots that took thousands of lives and properties. The objective of this research is to find out the form of the cultural acculturation occurring between Balinese transmigrants with the Dayak Ngaju in Basarang Jaya Village. This research used phenomenology approach. The data were collected through in-depth interviews and participatory observations. The sources of research data are the local chiefs of Balinese and banjar Bali in Basarang Jaya Village and the first group of transmigrants coming to Basarang Jaya Village. The subject of the research was the Balinese transmigrants in Basarang Jaya Village. The object of the research is the way of life, the way of speaking, the food and the religious activities of Bali transmigrants. The research reveals some facts. First, the Balinese transmigrants have made adaptation by imitating how the ethnics of Dayak Ngaju lives. Second, there are changes in the language, way of life, food and religious activities of transmigrants. Third, the harmony between the two ethnics can be maintained by using the religion as the medium of integration.